The Development Study of Adisutjipto International Airport, Special Region of Yogyakarta - Eis , Ariska Harselinda; Ahyudanari, Ervina (Jurnal Transportasi: Sistem, Material, dan Infrastruktur, 2023)
Adisutjipto International Airport is one of the airports in Yogyakarta, besides the newest airport, Yogyakarta International Airport (YIA) Kulon Progo. The existence of passenger density of up to 8 million/year at Adisutjipto International Airport, and there will be flight diversions to YIA. Therefore, Adisutjipto International Airport needs to improve by developing the airport from the air side (runway, taxiway, and apron) to the land side (terminal). This development study used secondary data with linear regression of forecasting data for the next five years. Furthermore, this study reviews the runway's capacity at the time before the transfer of jet-type aircraft and after the transfer was carried out earlier in 2020 from the 2021 plan year to YIA. Furthermore, analysis and calculation of the runway, taxiway, and apron dimensions were carried out using the results of the existing forecast data on the planned aircraft, namely the Aircraft A320. Based on the analysis, it was found that 2500m x 60m (including shoulders) of runway dimension requirements. In addition, there was an additional runway length of 250m toward runway 09, and the dimensions of the taxiway width are 45m (including shoulders). The location of the exit taxiway was 1581m from the threshold. Meanwhile, the apron dimensions (1303.618m x 126.992m). On the land side, the total terminal area is 195623.1m2. After the development study was carried out, in the KKOP analysis, it can be concluded that it is still suitable for flight operations. Furthermore, the latest analysis regarding transferring from jet-type aircraft to YIA (29 March 2020) shows that Adisutjipto International Airport does not need airport development. It was because the runway capacity will be 14 operations/hour in 2025, while during peak hours, it will get 13 operations/hour.